Effect of beta blocker therapy on survival in severe heart failure (Faculty of Medicine Universitas Indonesia, 2002)
Beta-blocking agents have been shown to reduce the risk of hospitalization and death in patients with mild to moderate heart failure, but little is known about the efficacy or safety of these agents in severe heart failure. A case of beta blocker administration in severe heart failure with ejection fraction less than 25% is reported. The reported benefits of beta blockers with regard to morbidity and mortality in patients with mild to moderate heart failure were also found in the patient with severe heart failure as reported in this case. (Med J Indones 2002; 11: 174-5) Keywords: beta-blocking agents, heart failure, ejection fraction